CHILDREN’S MUSIC EDUCATION IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Isroilov Abdurahim Ismoilovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article provides feedback on children’s music education in preschools.